(untitled) (Scientific journal of the Fergana State University, 2024)
This article focuses on the issues of filling the need for specialist personnel for the development of the textile industry, which is a branch of light industry in Uzbekistan. The existence of a special role of the Bukhara textile industry in the development of the country’s economy and the important role of qualified specialists, including women in the textile industry, and the issues of gaining experience in the textile factories established in the regions of Uzbekistan regarding their qualification are described. At the same time, information about the history of the opening of light industry technical schools and family schools in Bukhara is given.